2010
DOI: 10.1074/jbc.m110.142141
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Activation of Matrix Metalloproteinase-13 Transcription Requires the Histone Acetyltransferase Activity of p300 and PCAF and p300-dependent Acetylation of PCAF

Abstract: Parathyroid hormone (PTH) regulates the transcription of many genes involved in bone remodeling in osteoblasts. One of these genes is matrix metalloproteinase-13 (MMP-13), which is involved in bone remodeling and early stages of endochondral bone formation. We have previously shown that Mmp-13 gene expression is highly induced by PTH treatment in osteoblastic UMR 106-01 cells, as well as primary osteoblasts. Here, we show that p300/CBP-associated factor (PCAF), in addition to p300 and Runx2, is required for PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Under basal conditions, gene transcription of Mmp13 is repressed by the presence of HDAC4, which binds to Runx2 at the runt domain binding site (15). PTH treatment causes HDAC4 to dissociate from Runx2 on the Mmp13 promoter, and Runx2 then recruits the histone acetyltransferases, p300 and PCAF (13,14). Newly synthesized c-Fos/c-Jun subsequently bind to the AP-1 site and interact with CBP and with proteins bound to Runx2, allowing maximal transcription of Mmp13 (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under basal conditions, gene transcription of Mmp13 is repressed by the presence of HDAC4, which binds to Runx2 at the runt domain binding site (15). PTH treatment causes HDAC4 to dissociate from Runx2 on the Mmp13 promoter, and Runx2 then recruits the histone acetyltransferases, p300 and PCAF (13,14). Newly synthesized c-Fos/c-Jun subsequently bind to the AP-1 site and interact with CBP and with proteins bound to Runx2, allowing maximal transcription of Mmp13 (58).…”
Section: Discussionmentioning
confidence: 99%
“…In response to PTH, Mmp13 gene transcription was significantly attenuated by mutation of AP-1 binding sites (12). We have previously shown that PTH stimulation of MMP13 expression is regulated by histone acetylases p300, p300/CBPassociated factor (PCAF), and histone deacetylase 4 (HDAC4) (13)(14)(15).…”
Section: Parathyroid Hormone (Pth)mentioning
confidence: 99%
“…Runx2 complex, together with co-regulatory factors SMADs and other co-activator and co-repressor proteins, regulate target gene transcription (36). p300, a histone acetyltransferase, has been reported to interact with Runx2 and to subsequently regulate the expression of osteocalcin and MMP-13 (37,38). In addition, p300 also acts as a stabilizer of Runx2 via acetylation (39).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic overexpression of Wdr5 using a 2.3-kb α (1)I-collagen promoter induced accelerated osteoblast and chondrocyte differentiation resulting in substantially increased endochondral bone growth suggesting [63]. Several other acetyltransferases have been implicated in epigenetic regulation of bone formation, osteoblast-related gene expression or deregulated in osteoarthritis including PCAF (KAT2B) [60, 64], MOZ/MORF (KAT6A/KAT6B) [65, 66], and the circadian-rhythm specific acetyltransferase: Clock (KAT13D) [67]. …”
Section: Introductionmentioning
confidence: 99%